Utilisation of Vignettes Instructional Method and Ethical Sensitivity in Decision-Making among Business Studies Teacher Trainees at the University of Nairobi, Kenya - Mary Prisca Oluoch; Paul Amollo Odundo; John Kamau Mwangi (Journal La Edusci, 2021)
Vignettes have been applied in many academic disciplines over time, as an essential element of experiential learning. At the Department of Educational Communication and Technology, adoption of vignettes instructional method by instructors remains slow, while application by early adopters remains inconsistent. Despite this, little is known about how utilisation of vignettes to teach business ethics at the Department influences teacher trainees’ ethical sensitivity in decision-making. The cross-sectional survey design guided the research process, and primary data were sourced in 2018 from 116 learners. Both quantitative and qualitative analysis techniques were applied. Key results show that trainees who strongly agreed that utilisation of vignettes influenced their ethical sensitivity in decision-making had about 2 times the odds of being ethically sensitive in their decisions as their colleagues who expressed strong disagreement about the same. Besides, those who agreed that utilisation of vignettes influenced their ethical sensitivity in decision-making were about 1.9 times as likely to make ethically sensitive decisions as those who indicated strong disagreement. On aggregate, utilisation of vignettes caused a positive and significant influence on trainees’ ethical sensitivity in decision-making. It also emerged third in the order of relative importance. Notably, the more the trainees appreciated that utilisation of vignettes influenced their ethical sensitivity in decision-making, the higher odds of making ethically sensitive decisions. Thus, improving trainees’ knowledge on the various parameters of vignettes’ utilisation is likely to enhance their ethical sensitivity in decision-making. This may be achieved by dedicating a section of training modules on optimisation of vignette utilisation.